Cost-Benefit Analysis to Hedge with Third Party Producers in Demand-Driven Production - Hussain, Omar; Dillon, Tharam S. (Springer, 2010)
One of the characteristics of Demand-Driven Production is that goods should be manufactured and delivered to customers within the specified pe-riod of time. Manufacturers achieve this by utilizing various efficient production planning, scheduling tools and techniques. But situations may arise where the manufacturer, despite such techniques, may not be able to meet the required de-mand. So strategies need to be developed by which situations like these are coun-tered and the financial loss from them alleviated. One such strategy is to hedge the production of goods from third party producers. But before doing so, the manufac-turer has to carry out a cost-benefit analysis that will determine the feasibility and viability of considering this option. In this chapter, we propose a methodology by which the manufacturer does the cost-benefit analysis and then makes an informed decision about whether to hedge with third party producers.